The Contribution of Kurī (Polynesian Dog) to the Ecological Impacts of the Human Settlement of Aotearoa New Zealand - Greig, Karen; Rawlence, Nicolas J. (Frontiers in Ecology and Evolution, 2021)
The pre-human Aotearoa New Zealand fauna was dominated by avian and reptilian species. Prior to first human settlement by East Polynesian colonists, the top predators were two giant raptorial birds. Aside from humans themselves, colonisation also resulted in the simultaneous introduction of two novel mammalian predators into this naive ecosystem, the kiore (Pacific rat) and kurī (Polynesian dog). While the ecological impacts of kiore are relatively well understood, those of kurī are difficult to assess, and as such kurī have frequently been disregarded as having any meaningful impact on New Zealand’s biodiversity. Here we use the archaeological and palaeoecological record to reassess the potential impacts of kurī on this ecosystem. We argue that far from being confined to villages, kurī could have had a significant widespread but relatively localised impact on New Zealand’s avian, reptilian and marine mammal (seals and sea lions) fauna as a novel predator of medium-sized species. In this way, kurī potentially amplified the already significant impacts of Polynesian colonists and their descendants on New Zealand’s ecosystem, prior to European arrival. As such, kurī should be included in models of human impact in addition to over-hunting, environmental modification and predation by kiore.